Introduction - Afonso, Aline (2015)
This book gathers five papers presented to the ECAS’ 2013 proceedings. Following the theme of the Congress “African dynamics in a multipolar world”, the challenge was to select among the 118 papers presented those which focused in the subjects of informality and space reconfiguration. The papers were selected from 4 panels: “Writing the world from another African metropolis: Luanda and the urban question”, “Urbanisation and poverty in mining Africa”, “Urban imaginaries in Africa” and “Managing other people’s money: financial services in sub-Saharan Africa after structural adjustment”. In the editing process, we assumed that the intention of the authors when submitting papers to the ECAS’ proceedings was to share and collect contributions from the academic community to improve their researches. This means that all the papers in this book are considered a work in progress. The editor’s work, guided by the reviewers’ comments was limited: the main goal was to present the preliminary insights. The authors are therefore expecting to receive contributions from the readers and, thinking ahead, why not opening new communication channels?